Integrated Approach of Agri-nanotechnology: Challenges and Future Trends - Mishra, Sandhya; Keswani, Chetan; Abhilash, P. C.; Fraceto, Leonardo F.; Singh, Harikesh Bahadur (Frontiers in Plant Science, 2017)
Nanotechnology representing a new frontier in modern agriculture is anticipated to become a major thrust in near future by offering potential applications. This integrating approach i.e. agri-nanotechnology has great potential to cope with global challenges of food production/security, sustainability and climate change. However, despite the potential benefits of nanotechnology in agriculture so far, their relevance has not reached up to the field conditions. The elevating concerns about fate, transport, bioavailability, nanoparticles toxicity and inappropriateness of regulatory framework limit the complete acceptance and inclination to adopt nanotechnologies in agricultural sector. Moreover, the current research trends lack realistic approach that fail to attain comprehensive knowledge of risk assessment factors and further toxicity of nanoparticles towards agroecosystem components viz. plant, soil, soil microbiomes after their release into the environment. Hence in the present review we attempt to suggest certain key points to be addressed in the current and future agri-nanotechnology researches on the basis of recognized knowledge gaps with strong recommendation of incorporating biosynthesized nanoparticles to carry out analogous functions. In this perspective, the major points are as follows: (i) Mitigating risk assessment factors (responsible for fate, transport, behavior, bioavailability and toxicity) for alleviating the subsequent toxicity of nanoparticles. (ii) Optimizing permissible level of nanoparticles dose within the safety limits by performing dose dependent studies. (iii) Adopting realistic approach by designing the experiments in natural habitat and avoiding in vitro assays for accurate interpretation. (iv) Most importantly, translating environmental friendly and non-toxic biosynthesized nanoparticles from laboratory to field conditions for agricultural benefits.